A Novel RET D898Y Germline Mutation in a Patient with Pheochromocytoma. (15th April 2018) - Yi, Jin Wook; Kang, Hye In; Kim, Su-jin; Seong, Chan Yong; Chai, Young Jun; Choi, June Young; Seong, Moon-Woo; Lee, Kyu Eun; Park, Sung Sup
Abstract : Pheochromocytoma and paraganglioma are tumors of neuroectoderm origin. Up to 40% of patients with these tumors have germline mutations in known susceptibility genes. We report a novel RET germline mutation (exon 15; c.2692G>T (D898Y)) in a pheochromocytoma patient, as well as in her two asymptomatic sons and older sister. A 49-year-old female came to our clinic presenting with a right adrenal gland mass detected during a healthcare examination. Her mother and two sisters had previously undergone thyroidectomy for papillary thyroid carcinomas. The levels of vanillylmandelic acid and other catecholamines were elevated in 24-hour urine, and an imaging study revealed a right adrenal mass. She underwent laparoscopic adrenalectomy and the final pathologic diagnosis was pheochromocytoma. Mutation screening detected a RET p.D898Y mutation, both in the patient and in the patient's two sons and older sister. This is the first description of a RET D898Y mutation in a pheochromocytoma patient and her family. The mutation should be categorized as a variant of unknown significance because no RET gene related disorders were detected in this family. Long term follow-up will be required to determine the clinical significance of the RET D898Y mutation.